Product Rule for Derivatives

From ProofWiki
Jump to navigation Jump to search


Let $\map f x, \map j x, \map k x$ be real functions defined on the open interval $I$.

Let $\xi \in I$ be a point in $I$ at which both $j$ and $k$ are differentiable.

Let $\map f x = \map j x \map k x$.


$\map {f'} \xi = \map j \xi \map {k'} \xi + \map {j'} \xi \map k \xi$

It follows from the definition of derivative that if $j$ and $k$ are both differentiable on the interval $I$, then:

$\forall x \in I: \map {f'} x = \map j x \map {k'} x + \map {j'} x \map k x$

Using Leibniz's notation for derivatives, this can be written as:

$\map {\dfrac \d {\d x} } {y \, z} = y \dfrac {\d z} {\d x} + \dfrac {\d y} {\d x} z$

where $y$ and $z$ represent functions of $x$.

General Result

Let $\map {f_1} x, \map {f_2} x, \ldots, \map {f_n} x$ be real functions differentiable on the open interval $I$.


$\forall x \in I: \ds \map {D_x} {\prod_{i \mathop = 1}^n \map {f_i} x} = \sum_{i \mathop = 1}^n \paren {\map {D_x} {\map {f_i} x} \prod_{j \mathop \ne i} \map {f_j} x}$


\(\ds \map {f'} \xi\) \(=\) \(\ds \lim_{h \mathop \to 0} \frac {\map f {\xi + h} - \map f \xi} h\) Definition of Derivative
\(\ds \) \(=\) \(\ds \lim_{h \mathop \to 0} \frac {\map j {\xi + h} \map k {\xi + h} - \map j \xi \map k \xi} h\)
\(\ds \) \(=\) \(\ds \lim_{h \mathop \to 0} \frac {\map j {\xi + h} \map k {\xi + h} - \map j {\xi + h} \map k \xi + \map j {\xi + h} \map k \xi - \map j \xi \map k \xi} h\)
\(\ds \) \(=\) \(\ds \lim_{h \mathop \to 0} \paren {\map j {\xi + h} \frac {\map k {\xi + h} - \map k \xi} h + \frac {\map j {\xi + h} - \map j \xi} h \map k \xi}\)
\(\ds \) \(=\) \(\ds \lim_{h \mathop \to 0} \paren { \map j {\xi + h} \frac {\map k {\xi + h} - \map k \xi} h } + \lim_{h \mathop \to 0} \paren { \frac {\map j {\xi + h} - \map j \xi} h \map k \xi }\) Sum Rule for Limits of Real Functions
\(\ds \) \(=\) \(\ds \lim_{h \mathop \to 0} \paren { \map j {\xi + h} } \lim_{h \mathop \to 0} \paren { \frac {\map k {\xi + h} - \map k \xi} h } + \lim_{h \mathop \to 0} \paren { \frac {\map j {\xi + h} - \map j \xi} h } \lim_{h \mathop \to 0} \paren { \map k \xi }\) Product Rule for Limits of Real Functions
\(\ds \) \(=\) \(\ds \map j \xi \map {k'} \xi + \map {j'} \xi \map k \xi\) Definition of Derivative

Note that $\map j {\xi + h} \to \map j \xi$ as $h \to 0$ because, from Differentiable Function is Continuous‎, $j$ is continuous at $\xi$.


Also see

Historical Note

The Product Rule for Derivatives was first obtained by Gottfried Wilhelm von Leibniz in $1677$.